Tradeoff analysis between single and twin-aisle cross section for mid-size short-range aircraft. - Edmo Araujo das Virgens (2007)
The quest for comfort and mobility inside an aircraft is a daily concern. Today's designs are highly passenger-oriented, many times accepting performance losses as consequence of more spacious interiors. For wide-body twin-aisle aircraft there are a lot of solutions bringing an improved flying experience. On the other hand, the single-aisle paradigm for mid-size jets is far from being broken. The addition of one aisle in such aircraft would lead to a huge comfort and mobility improvement. Not only that, twin-aisle aircraft would have faster boarding and deplaning rates, diminishing the time on ground. Besides, the second aisle brings also cabin safety improvements. Considering that today everybody is seeking for performance gains, increasing the fuselage width to fit an extra aisle would seem to be running on the wrong way. However, the other intrinsic advantages might surpass these impacts and even lead the overall evaluation to a positive status. In order to measure and evaluate the impact of the addition of an extra aisle in mid-size short-range aircraft, a tradeoff analysis is conceived and described herein. Five main criteria are raised for the purpose of comparison. They are: comfort, accessibility, service, performance and cabin safety. Each analysis is presented along with its own criteria using distinct indicators. In the end, all results are compared. The differences, pros and cons are well depicted to the specific case study of mid-size short-range jets.